Trophic ecology of the smallnose fanskate Sympterygia bonapartii in the San Matías Gulf, northern Patagonia, Argentina - Estalles, María Lourdes (2016)
This study quantifies and describes the diet composition and variability, and the trophic ecology of Sympterygia bonapartii (Batoidea: Arhynchobatidae) in the San Matías Gulf, northern Patagonia, Argentina. A total of 1,047 stomachs were analyzed and 98 % of them contained food. The low proportion of empty stomachs recorded and the presence of prey in different stages of digestion suggested that this skate was a continuous feeder. A total of 81 prey items were identified. However, the diet was mainly composed of crabs. Other important groups in its diet were teleost fishes, shrimps and prawns, bivalves and worms. At the species level, the crab Peltarion spinosulum accounted for the highest contribution and the anchovy Engraulis anchoita ranked second in importance. By analyzing its diet composition, it was possible to classify S. bonapartii as a benthic predator, as are other skates reaching a similar maximum size. In addition, it was placed in the functional group of species that mainly feeds on decapod crustaceans. Trophic level was estimated at 3.61, indicating that the species was a secondary consumer. Significant differences were found in the diet according to sex, size class and season. These differences may be due to extrinsic and intrinsic factors that could be operating together.